2005
DOI: 10.1158/0008-5472.can-04-4114
|View full text |Cite
|
Sign up to set email alerts
|

Functional Analysis of PIK3CA Gene Mutations in Human Colorectal Cancer

Abstract: Mutations in the PIK3CA gene, which encodes the p110A catalytic subunit of phosphatidylinositol 3-kinase (PI3K), have been reported in human cancers, including colorectal cancer. Most of the mutations cluster at hotspots within the helical and kinase domains. Whereas H1047R, one of the hotspot mutants, is reported to have elevated lipid kinase activity, the functional consequences of other mutations have not been examined. In this study, we examined the effects of colon cancer-associated PIK3CA mutations on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
312
2
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 349 publications
(329 citation statements)
references
References 25 publications
14
312
2
1
Order By: Relevance
“…Similar to Mason et al (1999), we also observed a reduction of the activity of B-Raf wt proteins with a partial or neutralized N-region in some experiments, although this result could not be reproduced in all experiments as indicated by the comprehensive analysis in Figure 4a. As reported previously, B-Raf V600E displayed a robust MEK kinase activity, which was about 10-fold higher than that of B-Raf wt , a differential that has also been observed by other laboratories (Davies et al, 2002;Ikenoue et al, 2003Ikenoue et al, , 2004Grbovic et al, 2006). As expected from the aforementioned experiments in HEK293 and PC12 cells, this high activity was not considerably influenced by the R188L or S446/7A mutations.…”
Section: Regulation Of B-raf Signalling T Brummer Et Alsupporting
confidence: 87%
“…Similar to Mason et al (1999), we also observed a reduction of the activity of B-Raf wt proteins with a partial or neutralized N-region in some experiments, although this result could not be reproduced in all experiments as indicated by the comprehensive analysis in Figure 4a. As reported previously, B-Raf V600E displayed a robust MEK kinase activity, which was about 10-fold higher than that of B-Raf wt , a differential that has also been observed by other laboratories (Davies et al, 2002;Ikenoue et al, 2003Ikenoue et al, , 2004Grbovic et al, 2006). As expected from the aforementioned experiments in HEK293 and PC12 cells, this high activity was not considerably influenced by the R188L or S446/7A mutations.…”
Section: Regulation Of B-raf Signalling T Brummer Et Alsupporting
confidence: 87%
“…There is increasing evidence that the activation of PI3-K and its downstream effector Akt is associated with colorectal carcinoma, and can convert differentiated human gastric or colonic mucosa to a less differentiated, more malignant phenotype [18]. Both the regulatory (p85α) and catalytic (p110α) subunits of PI3-K play a role in colorectal cancers [19,20], and that there is a direct correlation between p85α and p110α staining intensity and the clinical stage of colon cancer [20,21]. Similar findings were reported in breast cancer [35].…”
Section: Discussionmentioning
confidence: 99%
“…The levels of pAkt, a downstream effector of PI3-K, are elevated in PTHrP overexpressing cells [16]. Moreover, multiple studies have shown that levels of components of the PI3-K pathway are elevated in colon cancer vs. normal colon mucosa, and that these increases are more pronounced during colon cancer progression [17][18][19][20][21]. We therefore investigated whether there is a link between the levels of PTHrP, the integrin α6 and β4 subunits, and Akt in the LoVo cell xenografts and in human colorectal adenocarcinomas, to ask whether elevated levels of PTHrP and integrin α6 and β4 accompany the increased expression of PI3-K pathway components.…”
Section: Introductionmentioning
confidence: 99%
“…In certain lymphomas, NF-kB activation can also be triggered by the fusion protein mucosa-associated lymphoid tissue (MALT)1/c-IAP2; this protein activates NF-kB through ubiquitination of NEMO (Zhou et al, 2005a). A number of other transforming proteins have been shown to activate NFkB, such as Vav (Palmby et al, 2004), Pim-2 (Hammerman et al, 2004) and B-Raf (Ikenoue et al, 2003).…”
Section: Activation By Oncoproteinsmentioning
confidence: 99%